HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN KUALITAS HIDUP LANSIA DI PANTI SOSIAL TRESNA WERDHA - ', Azwan '; ', Herlina '; Karim, Darwin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Peer social support has an important role in the process of life and quality of life of the elderly, so that social support be highly influential element in helping resolve problems that occur in the elderly. The purpose of this research is to determine the relationship between peer social support and quality of life of the elderly in nursing home Khusnul Khotimah Pekanbaru. The design was descriptive correlation research with cross sectional approach. The sampling technique total sampling involving 52 respondents. This research used questionnaire for peer social support translated from the Social Provision Scale (SPS) and indonesian WHOQOL-BREF questionnaire for quality of life variable. The univariate analysis was conducted and the result showed that from 29 respondents who recaived positive peer social support, there were 22 respondents (75,9%) had high quality of life and 7 (24,1%) respondents had low quality of life. Respondents who had negative peer social support were 23, and from that number, 9 respondents (39,1%) had high quality of life and 14 respondents (60,9%) had low quality of life. Bivariate analysis was conducted by using chi-square test and the statistic showed p value (0,017) < alpha (0,05), which means that there is a correlation between peer social support and quality of life of elderly in nursing home Khusnul Khotimah Pekanbaru. Keywords : Elderly, quality of life, peer social support, WHOQOL-BREF